Penguatan Manajemen SOP Pelayanan Publik pada Kelurahan Jatimulya - Budi Rachmawati; Reni Yesi; Rumia Simanullang; Maryam Putri Lorenza; Muhammad Adam Januarizki (Pelita: Jurnal Pengabdian kepada Masyarakat, 2026)
Public services at the village level represent the frontline of administrative service delivery to the community. However, several problems were identified in Kelurahan Jatimulya, including inconsistent service procedures, limited understanding of Standard Operating Procedures (SOP) among village officials, and weak SOP management in public service delivery. These issues affected service effectiveness and community satisfaction. This community service program aimed to strengthen public service SOP management through structured assistance, socialization, and implementation of standardized procedures. The methods applied included initial service condition analysis, evaluation of existing SOPs, development and refinement of SOP documents, training for village officials, as well as monitoring and evaluation of SOP implementation. The results indicated an improvement in officials’ understanding of SOP functions and importance, the availability of more systematic and applicable public service SOP documents, and better service flow clarity and consistency. Strengthening SOP management positively impacted public service quality and provided a foundation for more effective, transparent, and sustainable service delivery at Kelurahan Jatimulya.